2017
DOI: 10.1111/dgd.12350
|View full text |Cite
|
Sign up to set email alerts
|

The world of epithelial sheets

Abstract: An epithelium is a layer of closely connected cells covering the body or lining a body cavity. In this review, several fundamental questions are addressed regarding the epithelium. (i) While an epithelium functions as barrier against the external environment, how is barrier function maintained during its construction? (ii) What determines the apical and basal sides of epithelial layer? (iii) Is there any relationship between the apical side of the epithelium and the apical membrane of an epithelial cell? (iv) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…The results reported in the present study indicate that β‐cells plated after trypsin dissociation under conditions that abolish or reduce cell–cell and cell–substrate interactions form intracellular compartments, which share morphological, biochemical and physiological properties with elsewhere described vacuoles developing in different epithelial cell types [Vega‐Salas et al., 1987; Gilbert and Rodriguez‐Boulan 1991; Honda 2017]. We showed that aggregated β‐cells or cells attached to laminin‐coated Petri dish have a reduced tendency to develop vacuoles when compared to isolated β‐cells and cultured in suspension.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results reported in the present study indicate that β‐cells plated after trypsin dissociation under conditions that abolish or reduce cell–cell and cell–substrate interactions form intracellular compartments, which share morphological, biochemical and physiological properties with elsewhere described vacuoles developing in different epithelial cell types [Vega‐Salas et al., 1987; Gilbert and Rodriguez‐Boulan 1991; Honda 2017]. We showed that aggregated β‐cells or cells attached to laminin‐coated Petri dish have a reduced tendency to develop vacuoles when compared to isolated β‐cells and cultured in suspension.…”
Section: Discussionsupporting
confidence: 83%
“…When removed from their original environment, cells encounter different changes, including loss of cell–cell and cell–substrate contacts as well as interaction with their extracellular matrix. In most cases, these changes lead to rearrangement of cytoplasmic and membrane components that impairs intracellular trafficking and disturbs cell polarity and identity [Honda 2017; Vaidziulyte et al., 2019]. One of the common traits seen in dissociated epithelial cells with loss of cell–cell and cell–substrate contacts is intracellular vacuolation.…”
Section: Introductionmentioning
confidence: 99%
“…E PITHELIA are abundant tissue types in metazoan organisms whose structure is established early in embryonic development (Honda 2017). Two defining properties of epithelia are that their constituent cells are (1) physically linked through adhesions to form a sheet, or layer of cells, with important barrier and compartmentalization functions; and (2) polarized across the sheet such that the protein composition on the outer/lumenal side (i.e., apical) of the sheet differs from that on the inner side (i.e., basal).…”
mentioning
confidence: 99%
“…MUC4 and MUC1, two transmembrane mucins, have been involved in wide-ranging studies in relation to their pathological implication in malignancies and other disease processes due to their overor mis-expression [31,32]. The epithelium separates multicellular animals from the external environment by means of its identity of a transversely connected layer of cells with apical-basal polarity [33]. Mucins were secreted early in the evolution of metazoan as part of transmembrane structures functioning in the protection, repairing and survival of epithelia in vertebrates [34].…”
Section: Discussionmentioning
confidence: 99%